2012
DOI: 10.1007/s00432-012-1293-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heat shock protein 27 as a radioresistance-related protein in nasopharyngeal carcinoma cells

Abstract: The data suggest that HSP27 is a radioresistant protein in NPC cells, and its upregulation may be involved in the NPC radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Expression of HSPB1 also correlated with tumor differentiation in esophageal squamous cell carcinoma 27. HSPB1 has been reported as a radioresistance-related protein in the NPC cell lines, inhibition of which enhanced radiosensitivity 28. Accordingly, the reduced expression of HSPB1 in the poorly differentiated might associate with the clinical relevance of the NPC histological types that differentiation in fact conferred a worse response to radiotherapy in endemic area 8.…”
Section: Discussionmentioning
confidence: 89%
“…Expression of HSPB1 also correlated with tumor differentiation in esophageal squamous cell carcinoma 27. HSPB1 has been reported as a radioresistance-related protein in the NPC cell lines, inhibition of which enhanced radiosensitivity 28. Accordingly, the reduced expression of HSPB1 in the poorly differentiated might associate with the clinical relevance of the NPC histological types that differentiation in fact conferred a worse response to radiotherapy in endemic area 8.…”
Section: Discussionmentioning
confidence: 89%
“…Radioresistant human NPC cell lines CNE2-IR and CNE1-IR cells as well as their corresponding radiosensitive cell lines CNE2 and CNE1 cells were previously established by us (36,37), and cultured with RPMI-1640 medium containing 10% FBS (Invitrogen). Radioresistant CNE2-IR and CNE1-IR cells were derived from parental CNE2 and CNE1 cells, respectively, by treating the cells with four rounds of sublethal ionizing radiation (36,37).…”
Section: Cell Linesmentioning
confidence: 99%
“…Radioresistant CNE2-IR and CNE1-IR cells were derived from parental CNE2 and CNE1 cells, respectively, by treating the cells with four rounds of sublethal ionizing radiation (36,37). Radiosensitive CNE2 and CNE1 cells, used as a control, were treated with the same procedure except sham irradiated.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPB1 overexpression has been correlated with risk in lung cancer [Guo et al, ; Xu et al, ], pancreatic cancer [Heinrich et al, ; Shiota et al, ], prostate cancer [Shiota et al, ] and ovarian cancer [Zhao et al, ], and is involved in interferon pathway activation in HBV‐associated hepatocellular carcinoma [Tong et al, ]. Several studies have demonstrated that HSPB1 is a chemoradiation‐related protein which may promote drug‐resistance and radioresistance in cancer therapy [Zhang et al, ; Xu et al, ; Pang et al, ]. Therefore, HSPB1 may also play a vital role in the genesis and progression of NPC.…”
Section: Discussionmentioning
confidence: 99%